Characterization of novel structural features in the lipopolysaccharide of nondisease associated nontypeable Haemophilus influenzae. - Landerholm, M; Li, J; Richards, J; Hood, D; Moxon, E; Schweda, E (2004)
Nontypeable Haemophilus influenzae (NTHi) is a common commensal of the human upper respiratory tract and is associated with otitis media in children. The structures of the oligosaccharide portions of NTHi lipopolysaccharide (LPS) from several otitis media isolates are now well characterized but it is not known whether there are structural differences in LPS from colonizing, nondisease associated strains. Structural analysis of LPS from nondisease associated NTHi strains 11 and 16 has been achieved by the application of high-field NMR techniques, ESI-MS, ESI-MSn, capillary electrophoresis coupled to ESI-MS, composition and linkage analyses on O-deacylated LPS and core oligosaccharide material. This is the first study to report structural details on LPS from strains taken from the nasopharynx from healthy individuals. Both strains express identical structures and contain the common element of H. influenzae LPS, L-alpha-D-Hepp-(1-->2)-[PEtn-->6]-L-alpha-D-Hepp-(1-->3)-[beta-D-Glcp-(1-->4)]-L-alpha-D-Hepp-(1-->5)-[PPEtn-->4]-alpha-Kdop-(2-->6)-lipid A, in which each heptose is elongated by a single hexose residue with no further oligosaccharide extensions. In the major Hex3 glycoform, the terminal Hepp residue (HepIII) is substituted at the O-2 position by a beta-D-Galp residue and the central Hepp residue (HepII) is substituted at O-3 by a alpha-D-Glcp residue. Notably, the strains express two phosphocholine (PCho) substituents, one at the O-6 position of alpha-D-Glcp and the other at the O-6 position of beta-D-Galp. Major acetylation sites were identified at O-4 of Gal and O-3 of HepIII. Additionally, both strains express glycine, and strain 11 also expresses detectable amounts of N-acetylneuraminic acid.